Nitrogen Use Efficiency in Rice Under Different Levels of Nitrogen and Mulching Materials - Adhikari, BB; Basnet, KB; Dahal, KR; Yadav, DN (Journal of the Institute of Agriculture and Animal Science, 2002)
A field experiment was conducted to study the effect of different levels of nitrogen and mulching materials on rice productivity in humid sub-tropical condition of Chitwan during rainy season of 2000 at IAAS, Rampur. The experiment was laid out in a Randomized Complete Block Design with four replications consisting of three levels (0, 50 and 100 kg/ha) of nitrogen without mulch, combination of 50 and 100 kg N with two levels (1.5 and 3 t/ha) of wheat straw, combination of two levels (50 and 100 kg/ha) of nitrogen with 3 t/ha of Cassia tora and 50 kg nitrogen with 3 t/ha of Ipomoea fistulosa. The variety of rice used in the experiment was Masuli. The result revealed that the application of wheat straw @ 3 t/ha assisted to lower pH of floodwater with both levels (50 and 100 kg/ha) of nitrogen. The maximum grain yield of rice (3.93 t/ha) was obtained in the treatment with 100 kg N plus 3 t of wheat straw mulch per hectare. This was significantly higher than rest of the treatments except that of 100 kg N and 3 t of Cassia tora mulch per hectare. Addition of 3 t of wheat straw mulch to 100 kg N per hectare assisted to increase the total number of grains per panicle and panicle length significantly in comparison to 100 kg N per hectare and control without mulch. J. Inst. Agric. Anim. Sci. 23:59-64